MUSEUM DAN PERPUSTAKAAN: SEBUAH ANALISIS TEMATIK DI GOOGLE SCHOLAR - Yunus Winoto; Reza Ardhian (Program Studi Perpustakaan dan Ilmu Informasi, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2022)
Responding to the times and technology, there are more opportunities to develop services from informationinstitutions. Not spared from it are museums and libraries. Therefore, it is considered important formuseums and libraries to always be connected and take collaborative action. The concept of collaborationis often carried with various terms such as GLAM which stands for gallery, library, archive, and museum or LAM or library, archive, and museum. To finalize the concept of cooperation and collaboration betweenmemory institutions or information institutions, further research is needed from academics who specifically examine the relationship between museums and libraries. How they collaborate and what makes the benefits can be felt by both parties. The research carried out can take advantage of current technology that can be accessed for free and easily, namely Google Scholar. This research will continue several other studies regarding thematic analysis of articles contained in Google Scholar. The applications used are Publish or Perish and VOSviewer which will be used as a means of visualizing data and analyzing themes. The research method used is qualitative with a thematic analysis approach. The results obtained, articles about museums and libraries on Google Scholar have related terms, such as “library”, “museum”, “manuscript”, “archive”, “manuscript”, and “collection”. There are 53 authors that appear in VOSviewer, and after manually searching and retrieving the top three articles, these names appear in the visualization.